Exploring whey and faba bean protein interactions at the oil-water interface: A combined drop tensiometry and microfluidicsstudy - Dionysios D. Neofytos; Katherine F. Grasberger; Anders Holste; Sandra B. Gregersen; Claus H. Christensen; Milena Corredig (Current Research in Food Science, 2025)
The interfacial properties of model oil–water interfaces stabilized by faba bean protein isolate (FPI), whey protein isolate (WPI), and their mixtures were investigated. Two complementary techniques, microfluidics-based analysis and drop tensiometry were employed to study the impact of protein mixing on interfacial tension, adsorption kinetics, and droplet stability. A microfluidic platform was used for droplet generation and single droplet analysis, assessing the impact of protein blending on droplet size and shape eccentricity after droplet generation. Drop tensiometry complemented the microfluidics-based analysis by evaluating interfacial tension and viscoelastic properties of the various interfaces. The presence of FPI altered WPI interfaces; in mixed systems, antagonistic interactions between proteins resulted in a decreased elastic modulus and broadening of the shape eccentricity. Mixed systems resulted in smaller droplets with narrower size distributions and increased resistance to short-term coalescence with respect to emulsion droplets stabilized by FPI alone, and droplet stability increased proportionally with WPI/FPI ratio.